Restructuring of an RNA polymerase holoenzyme elongation complex by lambdoid phage Q proteins - Marr, Michael T. (The National Academy of Sciences, 2001)
The structure of an intermediate in the initiation to elongation transition of Escherichia coli RNA polymerase has been visualized through region-specific DNA cleavage by the hydroxyl radical reagent FeBABE. FeBABE was tethered to specific sites of the σ(70) subunit and incorporated into two specialized paused elongation complexes that obligatorily retain the σ(70) initiation subunit and are targets for modification by lambdoid phage late gene antiterminators. The FeBABE cleavage pattern reveals structures similar to open complex, except for notable changes to region 3 of σ(70) that might reflect the presence of stably bound transcript. Binding of the antiterminator protein Q displaces the reactivity of FeBABE conjugated to region 4 of σ(70), suggesting that σ(70) subunit rearrangement is a step in conversion of RNAP to the antiterminating form.